Tryptophan hydroxylase(2) gene polymorphisms predict brain serotonin synthesis in the orbitofrontal cortex in humans - Booij, L; Turecki, G; Leyton, M; Gravel, P; Lopez De Lara, C; Diksic, M; Benkelfat, C (Molecular psychiatry, 2012)
Brain regional serotonin synthesis can be estimated in vivo using positron emission tomography (PET) and α-[((11))C]methyl-L-tryptophan ((11)C-AMT) trapping (K*) as a proxy. Recently, we reported evidence of lower normalized (11)C-AMT trapping in the orbitofrontal cortex (OBFC) of subjects meeting the criteria for an impulsive and/or aggressive behavioral phenotype. In this study, we examined whether part of the variance in OBFC serotonin synthesis is related to polymorphisms of the gene that encodes for the indoleamine's rate-limiting enzyme in the brain, tryptophan hydroxylase-2 (TPH(2)). In all, 46 healthy controls had PET (11)C-AMT scans and were genotyped for 11 single-nucleotide polymorphisms (SNPs) distributed across the TPH(2) gene and its 5' upstream region. Several TPH(2) SNPs were associated with lower normalized blood-to-brain clearance of (11)C-AMT in the OBFC. Dose-effect relationships were found for two variants (rs6582071 and rs4641527, respectively, located in the 5' upstream region and intron 1) that have previously been associated with suicide. Associations in the OBFC remained statistically significant in a mixed larger sample of patients and controls. These results suggest that in humans, genetic factors might partly account for variations in serotonin synthesis in the OBFC.